THE CORRELATION OF PARITY AND MATERNAL AGE WITH THE INCIDENCE OF ABORTION - Deliana Deliana; Siti Rahayu (ALINEA: Health Science & Medical International Journal, 2024)
Background: Abortion refers to the deliberate termination or evacuation of a pregnancy before the gestational age reaches 20 weeks or the fetal weight is below 500 grams, preventing the fetus from surviving outside the uterus. One danger associated with abortion is the higher likelihood of multiple pregnancies and more frequent abortions in women between the ages of 20 and 35. Objective: The study aimed to establish the correlation between parity and maternal age and the occurrence of abortion. Method: This study employed an analytical research design with a case-control methodology. Utilizing the entire sampling technique for sampling. The study was carried out from December 2023 to February 2024 and included 242 pregnant women in Frisdhy Angel Hospital Batam city. Assessed using the Chi-Square statistical test. Result: This study discovered a statistically significant correlation between parity and the occurrence of abortion, with a ρ value of 0.002 < α 0.05. Additionally, there was a statistically significant correlation between age and the occurrence of abortion, with a ρ value of 0.001 < α 0.05. Conclusion: This study concludes that there is a correlation between the number of times a woman has given birth (parity) and her age at the time of pregnancy (maternal age) with the occurrence of abortion at Batam City Hospital.